Edukasi Pentingnya Menjaga Kesehatan Mata Di Era Digital - Johan B. Bension; Laura B. S. Huwae; Syalvira N. Nasaruddin; Mutia F. Tala; Laury M. Ch. Huwae; Ronald D. Hukubun (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
The development of information and communication technology has influenced every aspect of human life. Smartphones, computers, and tablets have become everyday tools that we rely on for various purposes. However, the high dependence on digital devices also brings new challenges, including negative impacts on physical and mental health, particularly eye health. This research aims to educate 5th grade elementary school students about the importance of maintaining eye health in the digital age through the method of socialization. The research method involves socializing with 5th grade students using educational materials tailored to the children's level of understanding. The socialization activities include interactive presentations, question and answer sessions, and demonstrations of simple eye exercises. After participating in the socialization, students showed a significant increase in understanding regarding the negative impacts of excessive digital device use on eye health. The results of this research highlight the importance of ongoing educational programs and collaboration between various parties to create a healthier digital environment and support eye wellness for all users.